The perception of young learners towards "walking phrase" activity: is it effective in engaging them in English phrase reading and sentence writing? / Norhasni Mohd Amin and Noraziah Mohd Amin - Mohd Amin, Norhasni; Mohd Amin, Noraziah (Academy of Language Studies, 2019)
Learning sentence structure is usually not seen as an enjoyable learning experience, while writing is a complex system of communication, which means learning how to write can pose some difficulties. Thus, "Walking Phrase" activity was introduced to 26 young learners of Sekolah Kebangsaan Seri Wangsa as a technique for engaging them in reading phrases and writing sentences. The objective of this study was to investigate the perception of these young learners towards the use of "Walking Phrase" as an effective strategy in engaging them in English phrase reading and sentence writing. "Walking Phrase" is a learning strategy that involves simple phrases and then learners try to use them in structuring sentences. As for the present study, the students each wore a phrase card. Then they read and memorized the short phrases written on the cards. The students then wrote the phrases in their writing booklets and also wrote complete sentences using the phrases. A questionnaire which comprised sixteen "Yes"/"No" questions was administered each of the 26 participants who were Year 6 students of the primary school in order to investigate their perception towards "Walking Phrase" activity. Based on the findings obtained, the majority of the students viewed "Walking Phrase" activity as an effective strategy in engaging them in reading phrases and writing sentences of English.